News Reports: Dalai Lama White House Visit
Off-air record of six TV shows and one radio program that cover His Holiness the Dalai Lama’s visit to the U.S. It includes the Dalai Lama’s appearance on CNN - Larry King Live Special, followed by Richard Gere and Tom Lantos; Dalai Lama interview on PBS - The News Hour with Jim Lehrer; ABC - World News Tonight with Peter Jennings; Fox News -Schneider Report; CNBC - Asia Market Wrap; NBC - Nightly News with Tom Brokaw; NPR - All Things Considered with commentator Sidney Jones.